An (Aminopyrimidinato)titanium Catalyst for the Hydroamination of Alkynes and Alkenes. Issue 33 (2nd October 2013) - Brahms, Christian; Tholen, Patrik; Saak, Wolfgang; Doye, Sven
Abstract: A new (aminopyrimidinato)titanium complex has been synthesised from inexpensive and easily accessible 2‐( tert ‐butylamino)pyrimidine and [Ti(NMe2 )4 ] and used as a catalyst for the intermolecular hydroamination of alkynes as well as the cyclization of aminoalkenes. The hydroamination reactions of 1‐phenylpropyne and terminal arylalkynes deliver the corresponding anti‐Markovnikov addition products with excellent yields and regioselectivities. Abstract : A new (aminopyrimidinato)titanium complex has been synthesised from inexpensive 2‐( tert ‐butylamino)pyrimidine and [Ti(NMe2 )4 ] and used as a catalyst for the intermolecular hydroamination of alkynes as well as the cyclization of aminoalkenes. The complex represents the first example of a catalyst for the hydroamination of alkynes that contains an aminoheteroaromatic ancillary ligand.